Greek and Roman animal sacrifice: ancient victims, modern observers ; [... conference 'The Centrality of Animal Sacrifice in Ancient Religion' at the Franke Institute for the Humanities at the University of Chicago in April 2008] - Faraone, Christopher A.; Naiden, F. S. (Cambridge University Press, 2012)
From Bergaigne to Meuli: how animal sacrifice became a hot topic / Bruce Lincoln -- One generation after Burkert and Girard: where are the great theories? / Fritz Graf -- Blessed are the parasites / F.S. Naiden -- Roman animal sacrifice and the system of being / John Scheid -- Sacrificing stones: on some sculpture, mostly Athenian / Richard Neer -- Sacrifice in Roman art / Jaś Elsner -- Animal sacrifice in comedy: an alternative point of view / James Redfield -- Animal sacrifice in Greek tragedy: ritual, metaphor, problematizations / Albert Henrichs